EXTRATROPICAL RESPONSE TO SST ANOMALIES AND THE BAROTROPIC MODEL - Palmer, T (Kluwer, for NATO/CEC, 1990)
Recent GCM integrations with El Nino sea surface temperature anomalies are reviewed, and the question of whether the extratropical response can be explained in terms of simple barotropic model dynamics is examined. -Author